Content Marketing Pada Instagram Happy Go Lucky House Dalam Membangun Brand Engagement - Hasanah, Nurul; Pamungkas, Indra Novianto Adibayu; Abdullah A, Nisa Nurmauliddiana (eProceedings of Management, 2023)
Digital marketing strategies are increasingly being applied by business people, this is in line with the rapid development of technology. Among them are content marketing implementation strategies that can be utilized to plan and distribute digital content on social media. One of the businesses that apply digital marketing with the application of content marketing is Happy Go Lucky House. Happy Go Lucky House is a pioneer of multibrand fashion concept stores in Indonesia, which has been established since 2008. This research aims to find out what Happy Go Lucky House does in an effort to build brand engagement on Instagram social media and how the utilization of content marketing is applied. The research method used is qualitative with an interpretive paradigm that can help researchers in making detailed descriptions that are factual and accurate. In an effort to obtain data, researchers used interviews, observation and documentation. The results showed that Happy Go Lucky House has utilized digital marketing with the application of content marketing on Instagram. However, there are some shortcomings where Happy Go Lucky House does not apply every dimension of content marketing according to Karr. This makes the brand engagement position of Happy Go Lucky House which can be said to be low.Keywords-Digital Marketing, Content Marketing, Brand Engagement, Instagram